Bonneviella gracilis Fraser 1939 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Bonneviella gracilis Fraser, 1939b Bonneviella gracilis Fraser, 1939b: 59, figs. 1a–c. Syntypes. BCPM 976-00454-001: Canada, Nunavut, Dease Strait, 25 July 1937, labelled " type "; 60% IPA. BCPM 976-00454-002: Canada, Nunavut, Dease Strait, 25 July 1937; slide. Lectotype, by present designation. RBCM 976-00454-003: Canada, Nunavut, Dease Strait, 40 fm (73 m), 25 July 1937, RCMP Vessel St. Roch, dredge, one colony fragment, attached to stolon of another hydroid species, 4 mm high, in good condition, without gonophores, coll. Sgt. H.A. Larsen; slide. Paralectotypes. BCPM 976-00454-001: Canada, Nunavut, Dease Strait, 40 fm (73 m), 25 July 1937, RCMP Vessel St. Roch, dredge, several colony fragments, in unsatisfactory condition, without gonophores, coll. Sgt. H.A. Larsen, labelled "type"; 60% IPA. BCPM 976-00454-002: Canada, Nunavut, Dease Strait, 40 fm (73 m), 25 July 1937, RCMP Vessel St. Roch, dredge, one colony fragment, attached to hydrocaulus of a sertulariid, 3 mm high, in good condition, without gonophores, coll. Sgt. H.A. Larsen; slide. Type locality. Canada, Nunavut: Dease Strait, 68°58’N, 106°20’W, 40 fm (73 m) (Fraser 1939b). Current status. Valid, but see Remarks below. Remarks. In the absence of a type designation of Bonneviella gracilis by Fraser (1939b), a name-bearing type has been selected from syntype material of the species in the Fraser Hydroid Collection at the RBCM (BCPM 976- 00454-001; BCPM 976-00454-002). The two samples are part of the same collection, obtained by Sgt. H.A. Larsen aboard the Royal Canadian Mounted Police vessel St. Roch while stuck in the ice in Dease Strait, Nunavut, Canada (Fraser 1939b). The best of the available specimens, designated here as the lectotype, is one of two colony fragments on a microscope slide (BCPM 976-00454-002). Occurring on the right side of the slide, it is attached to the stolon of another hydroid species. This specimen (RBCM 976-00454-003) consists of a hydrotheca with a largely intact hydranth, together with a hydrothecal pedicel and part of a ...